(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The aim of article to demonstrate the attributes of translation of journalistic materials in socio-political settings provided via examples in English and Uzbek languages. The study employed techniques such as descriptive method with its constituents - observation, interpretation, generalization; contextual analysis method; solid sampling strategy using actual material extracted from original texts. The analysis of translation of socio-political terms showed that the translator should pay attention to the translation of abbreviations, attributive expressions, stylistic expressive means and devices, socio-political terminology, phraseology, informal vocabulary.